Analisis Manajemen Mutu Terpadu Prof Saggaf dalam pandangan Islam - Robati, Kisti; Hariyanto (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
There are still aspects of the TQM (Total Quality Management) concept that do not align with Islamic principles. Therefore, the researcher will analyze the TQM principles presented by Prof. Assagaf in order to derive a more suitable concept. This research is a library study that emphasizes the analysis of literature from verses, hadiths, and other relevant sources. The results of this study indicate that the principle of prioritizing customer satisfaction is not fully in line with Islam; instead, it should prioritize self-improvement, followed by internal customers, and then external customers. The concepts of satisfaction and quality should also be adjusted to Islamic principles. As for the principle of respecting employees, it can be implemented if the concept of taqwa (piety) is practiced, selecting appropriate members and humanizing individuals, while not excluding the possibility of sanctions if necessary. Fact-based management can be applied if a team is formed to collect facts, process them, and use them in the improvement process, without neglecting human performance tendencies. To achieve continuous improvement maturity, generational development is necessary, and the PDCA (Plan-Do-Check-Act) program should be practiced along with subsequent improvements. This process should involve all parties, with each playing their respective roles.